2020
DOI: 10.3390/ijms21197069
|View full text |Cite
|
Sign up to set email alerts
|

Human Fibroblasts In Vitro Exposed to 2.45 GHz Continuous and Pulsed Wave Signals: Evaluation of Biological Effects with a Multimethodological Approach

Abstract: The increasing exposure to radiofrequency electromagnetic fields (RF-EMF), especially from wireless communication devices, raises questions about their possible adverse health effects. So far, several in vitro studies evaluating RF-EMF genotoxic and cytotoxic non-thermal effects have reported contradictory results that could be mainly due to inadequate experimental design and lack of well-characterized exposure systems and conditions. Moreover, a topic poorly investigated is related to signal modulation induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Dosimetry simulations are conducted on various regions of human head to measure RF EMFs at 835MHz-1.9GHz frequency range and there was uncertainty of head morphology to RF EMF exposures [47]. The experimental results of non-thermal biological effects at cellular and molecular level induced by 2.45GHz EMF exposures did not induce any significant biological effects [48]. Exposure to RF-EMFs generated by BSs and their impact on cognitive functions show that exposure of human lymphocytes to 900MHz frequencies used in MS for 30minutes does not significantly impact DNA integrity [49], [50].…”
Section: Results With Conflicts Of Interestmentioning
confidence: 99%
“…Dosimetry simulations are conducted on various regions of human head to measure RF EMFs at 835MHz-1.9GHz frequency range and there was uncertainty of head morphology to RF EMF exposures [47]. The experimental results of non-thermal biological effects at cellular and molecular level induced by 2.45GHz EMF exposures did not induce any significant biological effects [48]. Exposure to RF-EMFs generated by BSs and their impact on cognitive functions show that exposure of human lymphocytes to 900MHz frequencies used in MS for 30minutes does not significantly impact DNA integrity [49], [50].…”
Section: Results With Conflicts Of Interestmentioning
confidence: 99%
“…A 2020 study comprehensively evaluated the effect of RF-EM on human fibroblasts using high-throughput next-generation sequencing and biomarker analysis. 22 Experiments subjected human fibroblasts to continuous and pulsed signals of 2.45 GHz for 2 hours. There were no significant changes in the different phases of the cell cycle 2 and 24 hours postexposure when compared with control groups.…”
Section: Radiofrequency Electromagnetic Radiation Affects Metabolism ...mentioning
confidence: 99%
“…Although the levels of RF exposure from WLAN devices are far below the international limits-the exposure limit for the whole body is 0.08 W/kg, for the head, it is 2 W/kg, and 4 W/kg for the limbs [2,15]-it is important to research the potential health risk below and above these limits as well. In an in vitro study, Regalbuto et al reported that 2450 MHz does not induce genotoxic and cytotoxic effects on fibroblasts at a SAR of 0.7 W/kg [16]. Schuermann et al suggested that the possible carcinogenicity of modulated electromagnetic fields (i.e., GSM, UMTS Wi-Fi, RFID) cannot be explained by an effect on genome integrity through direct DNA damage; however, nongenotoxic, indirect effects that may promote tumorigenesis cannot be ruled out [17].…”
Section: Introductionmentioning
confidence: 99%